Phosphorylation Signaling in APP Processing in Alzheimer’s Disease - Tao Zhang (International Journal of Molecular Sciences, 2019)
The abnormal accumulation of amyloid-β (Aβ) in the central nervous system is a hallmark of Alzheimer’s disease (AD). The regulation of the processing of the single- transmembrane amyloid precursor protein (APP) plays an important role in the generation of Aβ in the brain. The phosphorylation of APP and key enzymes involved in the proteolytic processing of APP has been demonstrated to be critical for modulating the generation of Aβ by either altering the subcellular localization of APP or changing the enzymatic activities of the secretases responsible for APP processing. In addition, the phosphorylation may also have an impact on the physiological function of these proteins. In this review, we summarize the kinases and signaling pathways that may participate in regulating the phosphorylation of APP and secretases and how this further affects the function and processing of APP and Aβ pathology. We also discuss the potential of approaches that modulate these phosphorylation-signaling pathways or kinases as interventions for AD pathology.